Cortical and Putamen Age-Related Changes in the Microvessel Density and Astrocyte Deficiency in Spontaneously Hypertensive and Stroke-Prone Spontaneously Hypertensive Rats - Ritz, Marie-Françoise; Fluri, Felix; Engelter, Stefan T.; Schaeren-Wiemers, Nicole; Lyrer, Philippe A. (Current Neurovascular Research, 2009)
Cerebral small vessel disease (SVD) is a major contributor to dementia in the elderly, and hypertension represents a major cause for developing the disease. However, little is known about its development and progression. Modifications of large cerebral arteries due hypertension are thought to participate to the development of small ischemic infarcts, but the status of the small vessels before the establishment of hypertension is not well defined. Using spontaneously hypertensive rats (SHR) and stroke-prone SHR (SP-SHR) as a models for SVD, we analysed the effect of hypertension on the microvasculature in the cortex and putamen, and on its relationship with astrocytes in animals aged 2 to 9 months. Compared with the normotensive Wistar-Kyoto rats (WKY), the densities of the collagen type IV-positive capillaries were significantly higher in both brain areas of young SHR and SP-SHR. In contrast, the expression of the astrocytic marker GFAP was significantly lower in these animals, whereas astrogliosis was observed after 6 months in their cortex only. To investigate if chronic hypoxia occurs due to the lower number of astrocytes in young SHR and SPSHR, we evaluated the levels of HIF-1.. in both brain regions. The accumulation of HIF-1.. was not observed at the youngest ages, but was apparent in neurons of 9-month-old SHR and SP-SHR. Our results indicate that the brains of young SHR and SP-SHR rats show evidence of cellular imbalance between microvessels and astrocytes at the neurovascular unit that may lead to their higher vulnerability to hypoxic events at older ages.
Keywords: astrocyte